Resolution of Bangladesh-India maritime boundary : model for South China Sea disputes? - Sam, Bateman (2014)
In a rare 'good news' story for regional maritime security, an international court has established the maritime boundary between Bangladesh and India. Could this be a model for the South China Sea disputes?